Trigger Finger Resulting from Excessive Hand Use Accompanied by Dyslipidemia, Hypertension, and Obesity with Risk Factors of Genetic and Dietary Pattern - Dasa Novita, Khuznita; Santika Oktaviana, Dea (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2024)
Trigger finger is an inflammation of the tendon or connective tissue between bones and muscles, which results in a painful sensation when the affected individual bends or extends the finger. In this case, the condition was identified at a primary health care facility in Malang City. A thorough medical history was collected to identify risk factors, followed by a home visit to further detect these risk factors. This case highlights the role and application of family medicine, given the complex interplay of biopsychosocial variables that necessitates comprehensive and holistic treatment.